Analisis Faktor Penyebab Insomnia pada Lansia dan Dampaknya terhadap Kesehatan Mental dan Fisik - Apriansyah Asgap; Putri Ramayanti; Khoirul Anwar; Muhammad Ikhsan; Lena Marianti (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Insomnia is one of the most common sleep disorders among the elderly, characterized by difficulty initiating or maintaining sleep. This condition significantly impacts mental and physical health, reducing the quality of life. This study aims to analyze the factors causing insomnia in the elderly, its effects on health, and literature-based solutions to address the issue. The method employed is library research, analyzing 15 reliable sources, including scientific journals and books, published between 2019 and 2024. The findings indicate that the main causes of insomnia in the elderly include circadian rhythm changes, chronic illnesses, psychosocial stress, medication use, sedentary lifestyle, and poor habits, such as technology usage before bedtime. This condition triggers various effects, such as depression, anxiety, cognitive decline, metabolic disorders, and increased risk of cardiovascular diseases. The proposed solutions involve multidisciplinary approaches, such as cognitive-behavioral therapy, stress management, and lifestyle adjustments. This study highlights the importance of holistic interventions to reduce the prevalence of insomnia among the elderly and improve their quality of life. By providing a better understanding of the causes and impacts, this research serves as a reference for healthcare practitioners, families, and communities to support the well-being of the elderly.